Transformação microbiana de diterpenos bioativos e avaliação do potencial biológico dos derivados obtidos - Porto, Thiago Sousa (2016)
The present work describes the processes of extraction, isolation, purification and structural elucidation of structural analogues of two diterpenes of the entpimaranes class (ent-pimara-8 (14) -dien-19-oic acid - AP and ent-8 (14), 15-pimaradiene - PI) which were obtained through biotransformation by the fungus Aspergillus ochraceus. At stages of extraction, isolation and purification of the substances were carried out using chromatographic methods, and the structural clarification was carried out with the aid of spectrometric methods (NMR 1 H, 13 C NMR, HMBC). The biotransformation of AP (1) for 72 hours gave rise to derivatives 2 and 3, while analogs 5, 6, 7 and 8 were obtained by incubating the PI (4) for a period of 120 hours. Chemical structures substrates and derivatives are shown in Figure I. Several diterpenes shown in Figure I have been evaluated against adult forms of Schistosoma mansoni and the inhibitory capacity of aortic artery contraction in rats when induced by phenylephrine and against the dihydroorotated enzyme Trypanossoma cruzi dehydrogenase (TcDHODH), an excellent pharmacological target for the discovery of new drugs against Chagas disease. With respect to these tests, the AP (1) demonstrated a great schistosomicidal potential, whereas metabolite 2 inhibited efficiently the contraction of the rat aorta. None of the diterpenes evaluated were capable of significantly inhibiting the TcDHODH enzyme.